Det auditive rum i Kædereaktioner - Frydendahl Ladefoged, Louise (Peripeti, 2015)
This article analyzes the sound image in the radio drama Kædereaktioner – en fantasi om Niels Bohr og atombomben from the theories of Donald McWhinnie, Andrew Crisell and Ib Poulsen concerning the elements of the radio drama. The goal is to examine how the listener perceives a work that is only auditory and also which elements are characteristic and key to a radio drama.